Hubungan Kekerabatan Kepiting Biola (Uca spp.) di Desa Lalombi Kecamatan Banawa Selatan Kabupaten Donggala Berdasarkan Karakter Morfologi - Biung, Yelsan Kanan; Budiarsa, I Made; Trianto, Manap; Kundera, I Nengah; Ashari, Abdul; Jayanti, Zulaikhah Dwi (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aims to analyze the phylogenetic relationships among six species of fiddler crabs (Uca spp.) found in Lalombi Village, Banawa Selatan Subdistrict, Donggala Regency, based on morphological characters. A descriptive-exploratory approach was employed, with purposive sampling to select representative specimens. Eighteen morphometric characters were measured from three individuals of each species: U. triangularis, U. perplexa, U. dussumieri, U. annulipes, U. tetragonon, and U. bellator. Data were analyzed using Principal Component Analysis (PCA) and UPGMA clustering with the aid of PAST software version 4.03. The PCA results revealed that carapace length (CL), anterior carapace width (ACW), and posterior carapace width (PCW) contributed significantly to total morphological variation. Cluster analysis indicated a close phylogenetic relationship between U. tetragonon and U. triangularis, as well as between U. perplexa and U. bellator. U. annulipes appeared intermediate between the two groups, suggesting a moderate level of relatedness. In contrast, U. dussumieri formed a distinct branch, likely due to its markedly larger body size compared to the other species. These findings affirm that morphometric characters are valuable in elucidating phylogenetic relationships within the genus Uca and support taxonomy based on morphological traits.